Workforce Development to Improve Access to Pain Care for Veterans: A Qualitative Analysis of VA-ECHO Participant Experiences - Soumya Subramaniam; Krysttel C. Stryczek; Sherry Ball; Lauren Stevenson; P. Michael Ho; David C. Aron (SAGE Publishing, 2022)
Background/Objective The prevalence of chronic pain and its links to the opioid epidemic have given way to widespread aims to improve pain management care and reduce opioid use, especially in rural areas. Pain Management Specialty Care Access Network-Extension for Community Health Outcomes (VA-ECHO) promotes increased pain care access to rural Veterans through knowledge sharing from specialists to primary care providers (PCPs). We explored PCP participants' experiences in VA-ECHO and pain management care. Methods This qualitative study is based on a descriptive secondary analysis of semi-structured interviews (n = 10) and 3 focus groups with PCPs participating in VA-ECHO from 2017-2019. A rapid matrix analysis approach was used to analyze participants' responses. Results VA-ECHO was an effective workforce development strategy for meeting PCPs' training needs by providing pain management knowledge and skills training (eg alternative care approaches and communicating treatment options). Having protected time to participate in VA-ECHO was a challenge for many PCPs, mitigated by leadership and administrative support. Participants who volunteer to participate had more positive experiences than those required to attend. Conclusions VA-ECHO could be used for meeting the workforce development needs of PCPs. Respondents were satisfied with the program citing improvement in their practice and increased confidence in providing pain management care to Veterans despite some challenges to participation. These findings offer insight into using VA-ECHO to meet the VHA's workforce development to improve Veterans' access to pain management care. The ECHO model presents opportunities for workforce development in large complex healthcare systems and garnering ongoing support for this training model is necessary for promoting workforce development for PCPs.